Marine Proteins and Peptides - Se-Kwon Kim (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Marine proteins and peptides have great potential application in developing pharmaceuticals, nutraceuticals, and cosmeceuticals. Proteins and peptides from marine sources are considered to be safe and inexpensive. Protein- and peptide-based drugs have been increasing in recent days to cure various diseases by serving multiple roles, such as antioxidants, anticancer drugs, antimicrobials, and anticoagulants. There are different marine sources (macroalgae, fish, shellfish, and bivalves), which possibly contain specific protein and peptides.